EFEKTIVITAS SISTEM E-FILING DAN RELAWAN PAJAK TERHADAP KEPATUHAN WAJIB PAJAK DI LINGKUNGAN PERGURUAN TINGGI - Ermadiani; Kesuma, Nilam (Journal of Management and Innovation Entrepreneurship (JMIE), 2025)
Enhancing taxpayer compliance is a key objective of tax authorities. The use of technology, such as the e-filing system, and human assistance through tax volunteers, are among the strategies implemented to improve the efficiency and accuracy of tax return filing. This quantitative study utilized primary data collected through questionnaires distributed to individual taxpayers who are employees at the Faculty of Economics, Universitas Sriwijaya. A total of 60 respondents were selected using purposive sampling from a population of 110. The data were analyzed using multiple linear regression with SPSS version 29. The findings indicate that both the implementation of the e-filing system and the presence of tax volunteers have a positive and statistically significant effect on taxpayer compliance in submitting annual tax returns. The results suggest that digital systems and supportive human resources play a vital role in enhancing tax compliance. Policymakers should continue to develop and promote these initiatives to further improve taxpayer behavior.